2022
DOI: 10.1158/2767-9764.crc-22-0303
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Derivatives of MBQ-167, an Inhibitor of the GTP-binding Proteins Rac/Cdc42

Abstract: Rac and Cdc42, are homologous GTPases that regulate cell migration, invasion, and cell cycle progression; thus, representing key targets for metastasis therapy. We previously reported on the efficacy of MBQ-167, which blocks both Rac1 and Cdc42 in breast cancer cells and mouse models of metastasis. To identify compounds with increased activity, a panel of MBQ-167 derivatives was synthesized, maintaining its 9-ethyl-3-(1H-1,2,3-triazol-1-yl)-9H-carbazole core. Similar to MBQ-167, MBQ-168 and EHop-097, inhibit a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Our group has developed and characterized MBQ-167, a dual Rac/Cdc42 inhibitor with cell proliferation inhibition at the nanomolar scale capable of reducing tumor growth and metastasis in HER2+ and triple-negative breast cancer cells and mouse models [ 14 , 15 , 22 , 24 ]. Herein, we demonstrate that treating trastuzumab-resistant SKBR3 or the GFP-HER2-BM trastuzumab-resistant metastatic cancer cell line with MBQ-167 reduces cell viability, cell migration and induces apoptosis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group has developed and characterized MBQ-167, a dual Rac/Cdc42 inhibitor with cell proliferation inhibition at the nanomolar scale capable of reducing tumor growth and metastasis in HER2+ and triple-negative breast cancer cells and mouse models [ 14 , 15 , 22 , 24 ]. Herein, we demonstrate that treating trastuzumab-resistant SKBR3 or the GFP-HER2-BM trastuzumab-resistant metastatic cancer cell line with MBQ-167 reduces cell viability, cell migration and induces apoptosis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [14] , female SCID mice were inoculated in the fourth right mammary fat pad with 5 × 10 5 cells/mL of GFP-HER2-BM cells in 1:1 Geltrex (Gibco™ Gel-trex™ LDEV-Free Reduced Growth Factor Basement Membrane Matrix Cat. A14132–02): serum free DMEM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously it was shown that inhibition of Rac1 negatively affects the migration of cancerous cells (Montalvo-Ortiz et al 2012 ; Kunschmann et al 2019 ; Medina et al 2022 ). Thus, we tested the potential of HV-107 to inhibit cell migration and extracellular matrix degradation.…”
Section: Discussionmentioning
confidence: 99%